Publishing world, networks and mediations: Editorial Rosario SA and the circuit of the Universidad Nacional del Litoral (1930-1950) (Quinto Sol, 2023)
The article follows the career of the Spanish bookseller Laudelino Ruiz in two moments in particular: the first, when he settled in the city of Rosario. There, at the beginning of the 1930s, he opened his own bookstore and publishing house, and soon became a cultural mediator of the region, an aspect that is verified in the relationship he forged with some of the professors at the National University of the Litoral and its area of influence. The second moment begins with the intervention at the University after the coup d'état of 1943. Several professors, exonerated from their positions, undertook, together with Ruiz, an editorial project called Rosario SA. This experience was set up as a response to the abrupt changes in the conditions and spaces of production and circulation of the subjects, who were forced to rearrange their social relationships of meaning, and to reorient networks to reinvent themselves in the sphere of the publishing world as mediating agents.
Keywords: trajectories; networks of sociability; mediations; university extensionism